Why don't Firms Hire Young Workers during Recessions? A Replication of Forsythe (The Economic Journal, 2022) - Jonathan Créchet; Jing Cui; Barbara Sadaba; Antoine Sawyer (Journal of Comments and Replications in Economics (JCRE), 2025)
We replicate results of Forsythe (2022) studying the cyclicality of individuals' labor market transitions conditional on their experience. Using Current Population Survey (CPS) data and state-level variations in the unemployment rate, this paper shows that the hiring probability of youths is more sensitive to business-cycle conditions than for experienced individuals. We replicate the key results in this paper by reconstructing the dataset using the IPUMS-CPS database (Flood et al. (2020)) and recoding the main regressions from scratch. We also conduct a robustness replicability analysis and show that the paper's main results are robust in terms of statistical significance to (i) extending the sample period from 1994-2014 to 1994-2019 and (ii) using metropolitan statistical area (MSA) level unemployment variation instead of state-level variation. These extensions reduce the magnitude of the main effects of interest, but the paper's key conclusions are unaffected.
https://doi.org/10.15456/j1.2025210.1943358304
Keywords: E24; J63; J64; 330; Worker flows; Business cycles; Life cycle